Scallop IKK1 Responds to Bacterial and Virus-Related Pathogen Stimulation and Interacts With MyD88 Adaptor of Toll-Like Receptor Pathway Signaling - Li, Lingling; Liu, Wenjuan; Fan, Nini; Li, Fangshu; Huang, Baoyu; Liu, Qian; Wang, Xiaomei; Zheng, Yanxin; Sang, Xiuxiu; Dong, Juan; Wang, Xiaona; Wei, Lei; et al. (Frontiers in Immunology, 2022)
IKK proteins are key signaling molecules in the innate immune system of animals, and act downstream of pattern recognition receptors. However, research on IKKs in invertebrates, especially marine mollusks, remains scarce. In this study, we cloned CfIKK1 gene from the Zhikong scallop (Chlamys farreri) and studied its function and the signaling it mediates. The open reading frame of CfIKK1 was 2190 bp and encoded 729 amino acids. Phylogenetic analysis showed that CfIKK1 belonged to the invertebrate IKKα/IKKβ family. Quantitative real-time PCR analysis revealed the ubiquitous expression of CfIKK1 mRNA in all scallop tissues and challenge with lipopolysaccharide, peptidoglycan, or poly(I:C) significantly upregulated the expression of CfIKK1. Co-immunoprecipitation assays confirmed the interaction of CfIKK1 with scallop MyD88 (Myeloid differentiation actor 88, the key adaptor of the TLR signaling pathway) via its N-terminal kinase domain. Additionally, CfIKK1 protein could form homodimers and even oligomers, with N-terminal kinase domain and C-terminal scaffold dimerization domain playing key roles in this process. Finally, the results of RNAi experiments showed that when the scallop IKK1 gene was suppressed, the expression of IRF genes also decreased significantly. In conclusion, CfIKK1 could respond to PAMPs challenge and interact with MyD88 protein of scallop TLR signaling, with the formation of CfIKK1 dimers or oligomers. At the same time, the results of RNAi experiments revealed the close regulatory relationship between IKK1 and IRF genes of scallop. Therefore, as a key signal transduction molecule and immune activity regulator, CfIKK1 plays important roles in the innate immune system of scallops.